EDUCATIONAL PRACTICES ON TEACHING PHYSICAL EDUCATION FOR STUDENTS WITH HEARING IMPAIRMENT IN THE CASE OF AMBO LAZARIST CATHOLIC SCHOOL FOR THE DEAF, AMBO, WESTERN ETHIOPIA - Habtamu Debasu Belay; Asnakech Yitayew Chekol (Adisam Publisher, 2025)
The main objective of this research is to investigate the educational practice of Physical Education for Students with hearing impairments at Ambo Lazarist Catholic School. Researchers employed mixed methods, specifically embedded design. The populations of the study were 58 Students with hearing impairments, 1 physical education teacher, and 2 school principals. Comprehensive and purposive sampling were used. Data gathering instruments were questionnaire and structured interview. The findings of this study indicated that the level of identification, teaching strategies, and opportunities at Ambo Lazarist Catholic School for the Deaf for students with hearing impairments is low. No audiologist knew about identifying the magnitude of hearing impairment in Students with hearing impairment, and the teaching strategies of the school had some hindrances like rigidity in their teaching methods. Although there is a commitment to developing the educational practice of physical education for students with hearing impairment in this particular school, there is still work to be done in the future, like the school’s practice of identifying students with hearing impairment, which needs further attention among all stakeholders, and awareness-creation strategies that should be designed for families and other stakeholders so that they can support and encourage the practice of physical education for Students with hearing impairment.